Mentored postdoctoral training in Zimbabwe: A report on a successful collaborative effort - Danai T. Zhou; Charles C. Maponga; Munyaradzi Madhombiro; Admire Dube; Runyararo Mano; Albert Nyamhunga; Ian Machingura; Justen Manasa; James Hakim; Z. Mike Chirenje; Tinashe Mudzviti; Charles Nhachi; et al. (AOSIS, 2020)
Low-and-middle-income countries (LMICs) have high disease burdens, necessitating increased research. However, LMIC research output constitutes only 2% of global total. To increase output, researchers must be capacitated. The University of Zimbabwe (UZ) and the University at Buffalo (UB), developed and implemented the AIDS International Research Training Program (AITRP), in 2008, that focused on graduate scholars. The subsequent HIV Research Training Program (HRTP), begun in 2016, and piloted post-doctoral training to enhance research productivity at UZ. This report discusses the collaboration. As of 2016, prospective candidates applied by submitting letters of intent, research proposals, curriculum vitae and biographical sketches. The scholars research training included hypothesis and project development, completion of grant applications, research project budgets, research presentations to diverse audiences and the application of advanced statistics to research data. The first cohort of five postdoctoral scholars were trained at UZ and UB, between 2016 and 2019. Through the formalized postdoctoral training approach, scholars identified areas of focus. In 2017, one of the scholars obtained a National Institutes of Health (NIH) Emerging Global Leader Award and is now a highly-rated researcher based in South Africa. A second scholar made NIH D43 and K43 grant applications, while the remaining three are academicians and early researchers at UZ. Although research output in Africa and many LMICs is low, it can be built through cooperation similar to the UZ-UB HRTP. This manuscript reports on an effort aimed at building individual and institutional research capacity in Zimbabwe. This can serve as a model for building other similar training programs.